BALANCING AUTONOMY, COMPASSION, AND RESPONSIBILITY IN END-OF-LIFE CARE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article explores end-of-life care and the ethical dilemmas associated with it in modern healthcare. End-of-life care aims to improve the quality of life of patients with life-limiting illnesses through palliative support, hospice services, pain management, and psychological assistance. Advances in medical technology have introduced complex ethical challenges, including euthanasia, withdrawal of life support, Do Not Resuscitate (DNR) decisions, and conflicts between patient autonomy and medical responsibility. The paper emphasizes the importance of compassionate communication, cultural sensitivity, and patient-centered decision-making to preserve dignity and comfort at the final stage of life.
Keywords: End-of-life care; palliative care; hospice care; euthanasia; assisted suicide; withdrawal of life support; DNR; patient autonomy; medical ethics; cultural perspectives; pain management; bioethics.